A problemática urbana brasileira diante da "Outra economia": considerações metodológicas sobre a apropriação do debate da economia popular solidária pela teoria crítica urbana - Evandro Luis Alves (2020)
In this paper, I seek to discuss a set of theoretical contributions brought by the debate dedicated to the so-called “popular solidarity economy” and the possible boundaries that this debate establishes with the Lefebvrian approach to the Brazilian urban problem. As a way of presenting this set of contributions, we used an exploratory and theoretical-conceptual research that aims to present to the reader how the specific literature dedicated to the subject brings a new look at a certain type of daily practices of social reproduction normally recognized as “informal”, “marginal” or “inferior” amidst the general dynamics of the urban economy and peripheral urbanization in Brazil. To address the Brazilian urban phenomenon, in addition to highlighting Henri Lefebvre's critical urban theory as a central aspect for a materialistic reading of urban studies, I highlight how the relationship between Brazilian urbanization and the condition of underdevelopment is synthesized in the Brazilian debate as part of a “Criticism of dualistic reason”. As for the appropriation of the debate of the popular solidarity economy itself, I seek to present the emergence of the “field of solidarity economy” in Brazil, some of its theoretical limitations and the synthesis about the relationship of this phenomenon with the dynamics of the urban economy that is promoted by “field of social economy”- above all in the figure of the Argentine economist Jose Luis Coraggio. I observe how Karl Polanyi's economic sociology, in particular his thesis on other “forms of economic integration”, is central to this phenomenon being interpreted as part of the social construction of a possible “other economy”. I conclude the text by suggesting that the solidarity-based popular economy reintroduces a material condition for the realization of what Lefebvre suggested to be a process of “urban revolution”, giving new meaning to a set of daily practices of exercising work and using urban land strongly present in life Brazilian life and renewing the search for alternatives for urban development in the context of Brazilian dependent capitalism.